The Concept of Marketing Activity of the Organizations in the Sphere of Services of Physical Education and Sports (Laisvalaikio tyrimai, 2013)
Every year physical activity and sport increasingly penetrate into people’s daily lives: everywhere the number of sports clubs and organizations increases, as well as the number of people attracted to sport. Assessing the volume of the Russian market of sports goods, experts give the numbers from 0.6 to 4 $ billion, the annual growth rate of 15–20 %. According to international experts, the Russian market of the sports goods and services is among the most promising. Despite the lack of precise data, we can say that this segment of the consumer market is currently in the process of active growth. This is facilitated by favourable macroeconomic factors, and changes in consumer preferences. The relevance of the research is determined by folding in modern sports markets trends, which together with a massive demand ensure that manufacturers of sports goods and services have huge profits, the possession of which conditions stiff competition. Winning the competitive struggle in the conditions of constant confrontation with rival manufacturers and sports organizations can only be resorted to marketing. Scientific innovation. Definition of criteria for the concept of marketing activities that lead to success of enterprises and organizations providing and selling services for physical training and sports. Practical innovation. Formulated scientific principles in the work can be used in the marketing policy of the organizations working in the sphere of sports. Interaction of consumers and firms seek for quality, which will improve the quality of life and ensure the conditions for a healthy lifestyle.Keywords: sports marketing, the market for physical education and sports.